PERCEIVED CYBERCRIME RISK: MODIFICATION OF THE TECHNOLOGY ACCEPTANCE MODEL ON GENERATION Z - Julina Julina; Desrir Miftah; Didin Hadi Saputra (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study attempts to examine the factors that influence the intention to use mobile banking. The decision to use new technology has been widely studied by applying the Technology Acceptance Model (TAM). The main variables in TAM are intention, perceived ease of use, perceived usefulness, and attitude. This study tries to add one more variable, namely the perception of risk of being exposed to cybercrime. Data were collected using a questionnaire adapted from previous studies. The data that has been collected is tested for validity and reliability for further analysis using Structural Equation Modeling (SEM). The results showed that the perceived ease of use had a positive and significant effect on attitudes and perceived usefulness. Another finding is that perceived usefulness affects attitudes and subsequently attitudes affect intentions to use mobile banking. The new variable added in this study, namely the perception of cybercrime risk has a negative and significant effect on intentions to use mobile banking. Based on the findings of this study, it is recommended that banks improve features that provide ease of use and are useful in conducting transactions using mobile banking. This will encourage the public to have a positive attitude and be supported by minimizing the risk of cybercrime, which will increase public interest in using mobile banking.